1000 let besed (A Thousand Years of Words) (Narodna in univerzitetna knjižnica, 2010)
Brižinski spomeniki, the oldest known preserved written text in the Slovenian language, and at the same time the oldest Latin record of the Slavic language, was written deep in the Middle Ages, around the year 1000. From that time, until the 15th century, manuscript texts, mostly ecclesiastical, were written. The first preserved printed text, a German leaflet with a rebellion motto in Slovenian (Le vkup, le vkup, uboga gmajna), dates from 1515. Thirty-five years later, Trubar's first two books, Katekizem and Abecednik, were published, and Slovenian became a literary language that for half a millennium up to the present has stood alongside other European and world languages. It has survived many state formations and writings and has developed into a modern, living language of art and science, despite the domination of other languages stronger in number of speakers. The Slovenian literature is distinguished by its expression, quality and diversity of literary genres and forms.The collection 1000 Years of Words: A History of Slovenian Language and Literature is intended for a wide range of users. It brings together the most important works of the Slovenian written cultural heritage, as well as critical texts and pictorial material.
A thousand years of words collection represents history of Slovenian language and literature and is intended for the widest circle of users. It was primarily designed as an educational tool for e-learning for primary and secondary school students and it will be further developed to become a teaching tool for university students and researchers. The most important works of Slovenian written cultural heritage will be continuously added to it. By digitizing library materials and the publication thereof on the dLib.si portal, free access to the oldest written works, critical texts and images will be provided.